2011
DOI: 10.1126/science.1200674
|View full text |Cite
|
Sign up to set email alerts
|

An Emerging Role of Zoos to Conserve Biodiversity

Abstract: Roughly one in seven threatened terrestrial vertebrate species are held in captivity, a resource for ex situ conservation efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
244
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(255 citation statements)
references
References 16 publications
0
244
0
3
Order By: Relevance
“…significant financial contributions to field conservation projects) (Gusset & Dick 2011). However, the way zoos contribute to conservation is still controversial: for instance, zoos mostly display large-bodied vertebrates and less-threatened species (Balmford et al 1995, Conde et al 2011, Fa et al 2014, Martin et al 2014. One reason for such bias toward large vertebrates is the general public preference for large mammals and rare or charismatic species in zoos (Angulo et al 2009, Ward et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…significant financial contributions to field conservation projects) (Gusset & Dick 2011). However, the way zoos contribute to conservation is still controversial: for instance, zoos mostly display large-bodied vertebrates and less-threatened species (Balmford et al 1995, Conde et al 2011, Fa et al 2014, Martin et al 2014. One reason for such bias toward large vertebrates is the general public preference for large mammals and rare or charismatic species in zoos (Angulo et al 2009, Ward et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Roughly one out of seven known threatened species on the planet can be found in a zoo or an aquarium (Conde et al, 2011) and captive breeding in such institutions may be the only practical conservation option left for some species whose habitats are dwindling. The authors showed that of 68 vertebrate species with improved conservation status as per their IUCN Red List designation, 13 species benefitted from conservation breeding with zoological institutions also contributing substantial logistical, technical or financial support for nine of those 13 species.…”
Section: Integration Of In-situ and Ex-situ Conservation Programsmentioning
confidence: 99%
“…Research has shown that zoos currently hold roughly one in seven (15%) threatened species of terrestrial vertebrates (Conde et al 2011).…”
Section: Noah's Ark In Rough Watermentioning
confidence: 99%